Peran Bhinneka Tunggal Ika Dalam Keberagaman Adat Budaya di Indonesia - Imam Riyadi; Edo Arya Prabowo; Dzikril Hakim (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
Bhinneka Tunggal Ika, which translates as "Diverse but also one", is Indonesia's national motto which represents the spirit of unity in diversity. This journal aims to analyze the function and role of the concept of Bhinneka Tunggal Ika in maintaining harmony and respecting the diversity of cultural traditions in Indonesia. It was found that Bhinneka Tunggal Ika acts as a foundation for building an inclusive national identity, respecting differences and celebrating cultural plurality. These findings provide a deeper understanding of how the concept of diversity is not just an empty slogan, but also a guiding principle in maintaining unity and tolerance amidst the complexity of Indonesian society. The implications of this research can contribute to the development of policies that support the maintenance and appreciation of cultural diversity in Indonesia. More than 500 Indonesian ethnic groups show their cultural diversity, which includes language, religion, science, kinship, social systems and government systems. local economic and political systems implemented. Over the years, the movement for "unity and unity" has been more than just incorporating differences into a container that allows for togetherness; more than that, it has been an ugly story about the various ways in which cultural expression is restricted.